Comparison of anticholinergic burden with chronic polypharmacy on functional decline and mortality in Korean older people: a retrospective nationwide cohort study - Youn Huh; Ye-Jee Kim; Jung-Yeon Choi; Ji Eun Lee; Hee-Won Jung; Cheol Min Shin; Chang Won Won; Ki Young Son (BMC Geriatrics, 2024)
Abstract Background We aimed to evaluate the association of anticholinergic burden and chronic polypharmacy with the incidence of functional decline and all-cause mortality, and to determine the difference between anticholinergic burden and chronic polypharmacy among Korean older people. Methods This nationwide cohort study included 42,132 older people aged ≥ 65 years who underwent Korean National Health Insurance Service health examinations from 2007 to 2008. Odds ratios (ORs) and 95% confidence intervals (CIs) for abnormal Timed Up and Go (TUG) test results were assessed using multivariate logistic regression analyses. Hazard ratios (HRs) and 95% CIs for all-cause mortality until the end of 2015 were estimated using multivariable Cox proportional hazards regression analysis. Results Of the participants, 37.19% had abnormal TUG test results, and 7.66% of those died during the 5.7-year mean follow-up. The abnormal TUG test results OR increased by 27% among individuals with Korean Anticholinergic Burden Scale (KABS) scores ≥ 3 (OR 1.27, 95% CI 1.02–1.58) compared to those with KABS scores of 0. The HRs for all-cause mortality increased for individuals with higher KABS scores (P for trend < 0.001) or chronic polypharmacy (P for trend < 0.001) compared to those for individuals without these conditions. The combination of a higher KABS or chronic polypharmacy and abnormal TUG test results increased the risk of all-cause mortality (All P for trend < 0.001). Conclusion Anticholinergic drug burden shows a better association with functional decline than chronic polypharmacy, and the use of medications and functional decline may be important risk factors for all-cause mortality among older people.